A Critical Public Relations Approach to Crisis Communication and Management A Case Study of Malaysia Airlines Flight MH370 Disappearance - Wang, Huabin (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book proposes a critical public relations approach to analyzing crisis communication with Malaysia Airlines flight 370 (MH370) disappearance (2014-2018) as a case study. It examines the discursive process of Malaysia's crisis response and image building, tracing Malaysia Airlines during the immediate response and the Malaysian establishment until the official suspension of the underwater search. The study features a critical discourse analysis of 84 national media texts and 85 response statements, focusing on three aspects: the national media representations of Malaysia's image, the national carrier and the government's rhetorical strategies of delivering stances and actions, and the dynamic process of image reconstruction and national recovery. The present project contributes to the current research area by integrating both linguistic and public relations perspectives, and more importantly, by highlighting the ideological impact instead of merely behavioral effectiveness in modern communication research. Target readers may find their interest in corporate crisis communication, critical inquiry about political public relations, and the MH370 incident in general.
Mh370 as a national PR case: controversy and challenges -- PR research on national crises: national image and crisis response -- Theoretical framework, research methodology and data -- Crisis framing and image restoration: national media representations of Malaysia's image in the Mh370 disappearance -- Communication practice and institutional power: discursive representations of crisis response in the mh370 disappearance -- Discussion and implications: discourse and PR practice.
Keywords: Sociolinguistics; Public relations; Intercultural communication; Communication; Sociolinguistics; Public Relations; Intercultural Communication; Media and Communication